Family Firm(s) Outcomes Model: Structuring Financial and Nonfinancial Outcomes Across the Family and Firm. (June 2017) - Holt, Daniel T.; Pearson, Allison W.; Carr, Jon C.; Barnett, Tim
Family firms are distinguished theoretically from nonfamily firms due to their pursuit of unique, family-related aspirations and goals. The pursuit of these aspirations and goals leads many family firms to define success or failure in terms of a broader set of outcomes than nonfamily firms. Despite this, family firm research has generally taken a constricted view of family firm outcomes by concentrating on narrowly defined financial performance as measured by accounting and/or market-based indicators. We contend that this somewhat myopic focus has slowed the field's development to some degree, by constraining our ability to test its fundamental tenets. To address this, we draw on several disciplines to systematically order family firm outcomes within a family firm(s) outcomes model that encompasses both financial and nonfinancial dimensions. While financial performance is important in research and practice, herein we refer to both financial and nonfinancial outcomes and explain how these outcomes map on the family unit and the family firm. Furthermore, we suggest measures that can be used and explain how the model can be applied when researchers select financial and nonfinancial outcomes important to family members as the family firm's success or failure is gauged.